2006
DOI: 10.1016/j.juro.2006.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Saturation Biopsy in the Reevaluation of Microfocal Prostate Cancer

Abstract: This study is to our knowledge the first to describe the clinical use of prostate saturation biopsies for re-evaluating potentially insignificant prostate cancer. Of patients with minimal disease on standard 10-core biopsy, results show that this technique may be helpful for distinguishing the 30% who probably have minimal disease based on negative repeat saturation biopsy from the 70% who almost certainly have a significant tumor, as characterized by multiple positive cores, with or without an increased Gleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…SPBx has been proposed as a staging tool for revaluating patients with microfocal PCa [13]. Boccon-Gibod et al [23] reported that in 34 patients submitted to repeat SPBx the presence of multifocal PCa and un-upgrading of GS was true in 70 and 20% of the cases, respectively. Moreover, in 55 patients with microfocal disease who underwent RRP after SPBx we detected a significant cancer in 85% of the cases, with presence of non-OC PCa in 27.3% of them [22].…”
Section: Discussionmentioning
confidence: 99%
“…SPBx has been proposed as a staging tool for revaluating patients with microfocal PCa [13]. Boccon-Gibod et al [23] reported that in 34 patients submitted to repeat SPBx the presence of multifocal PCa and un-upgrading of GS was true in 70 and 20% of the cases, respectively. Moreover, in 55 patients with microfocal disease who underwent RRP after SPBx we detected a significant cancer in 85% of the cases, with presence of non-OC PCa in 27.3% of them [22].…”
Section: Discussionmentioning
confidence: 99%
“…18,[21][22][23][24] The spectrum of prostate biopsy cores taken ranges from 6 to 80þ, yet it is not known how many cores are …”
Section: Patient Selectionmentioning
confidence: 99%
“…sufficient to assure that a clinically significant cancer will not be missed on the untreated side, 21,22,[24][25][26][27] Even a single positive core that is identified in low-risk PCa when obtained with routine transrectal biopsy techniques may not exclude bilateral disease in all instances. Barber and associates 28 investigated the data of 129 men with a single positive PCa core (in a 6-12 core biopsy), with 46 (36%) patients subsequently treated with RP.…”
mentioning
confidence: 99%
“…Recently, saturation prostate biopsy (SPBx: 24 or more cores) has been proposed [2] as a staging tool for evaluating patients with microfocal PCa characterized by a single microfocus (5% or less) of Gleason score (GS) 6 cancer on primary biopsy. Boccon-Gibod et al [3] first reported on the clinical use of repeat SPBx in 34 patients with a diagnosis of microfocal PCa on a 10-core biopsy set: SPBx was helpful in distinguishing the 30% of men who probably have minimal disease, on the basis of negative SPBx, from the 70% with multifocal disease (17 points) or grade 4 PCa (7 points)…”
Section: Introductionmentioning
confidence: 99%